1996
DOI: 10.1016/s0952-7915(96)80019-7
|View full text |Cite
|
Sign up to set email alerts
|

Virus-induced autoimmune disease

Abstract: The breaking of tolerance or unresponsiveness to self-antigens, involving the activation of autoreactive lymphocytes, is a critical event leading to autoimmune diseases. The precise mechanisms by which this can occur are mostly unknown. Viruses have been implicated in this process, among other etiological factors, such as genetic predisposition and cytokine activity. Several ways have been proposed by which a viral infection might break tolerance to self and trigger an autoreactive cascade that ultimately lead… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
89
0

Year Published

1997
1997
2001
2001

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 129 publications
(90 citation statements)
references
References 71 publications
(78 reference statements)
1
89
0
Order By: Relevance
“…The synthetic dsRNA molecule poly(I-C) has been shown to induce an antiviral response that is similar to the antiviral response activated following viral infection (8,16). Since viruses from both RNA and DNA genome families have been associated with the development of autoimmune diabetes (3,4), the synthetic dsRNA molecule, poly(I-C), was used to examine mechanisms of virally induced islet dysfunction and degeneration. In this study, we show that poly(I-C), in the presence of IFN-␥, stimulates iNOS expression and nitrite formation, inhibits insulin secretion, and induces rat islet degeneration by an IL-1-dependent mechanism.…”
Section: Il-1 Mediates Dsrna ϩ Ifn-␥-induced ␤-Cell Damagementioning
confidence: 99%
See 1 more Smart Citation
“…The synthetic dsRNA molecule poly(I-C) has been shown to induce an antiviral response that is similar to the antiviral response activated following viral infection (8,16). Since viruses from both RNA and DNA genome families have been associated with the development of autoimmune diabetes (3,4), the synthetic dsRNA molecule, poly(I-C), was used to examine mechanisms of virally induced islet dysfunction and degeneration. In this study, we show that poly(I-C), in the presence of IFN-␥, stimulates iNOS expression and nitrite formation, inhibits insulin secretion, and induces rat islet degeneration by an IL-1-dependent mechanism.…”
Section: Il-1 Mediates Dsrna ϩ Ifn-␥-induced ␤-Cell Damagementioning
confidence: 99%
“…Viruses have been isolated from pancreata, and virus-specific IgM antibodies have been identified in newly diagnosed diabetic patients (2,3). Diabetes can be induced in genetically susceptible strains of mice, rats, and primates by infection with encephalomyocarditis virus, Coxsackie B4 virus, Kilham's rat virus, rubella virus, and retrovirus (3,4). Encephalomyocarditis-induced diabetes in mice is associated with increased expression of iNOS 1 and macrophage-derived cytokines IL-1␤, IL-12, and TNF-␣.…”
mentioning
confidence: 99%
“…Other viruses, including retroviruses, cause a similar phenomenon. In human autoimmune diseases like multiple sclerosis (MS), insulin dependent diabetes mellitus (IDDM) or ankylosing spondylitis, the incidence of disease varies in monozygotic twins suggesting that factors other than genetic and likely environmental also play a role [3][4][5]. It has been observed that infectious agents [6][7][8] or cytokines [9][10][11][12] [3,[13][14][15].…”
Section: What Evidence Suggests That Viruses Are Implicated In Autoimmentioning
confidence: 99%
“…When the cytokine profile in the islet of Langerhans milieu was changed from a Th1 to a Th2 phenotype (g-interferon to IL-4, IL-10, TGFb), IDDM was blocked [4,5,40,46]. One interesting way this occurred was through the oral administration of porcine insulin [46,49,50].…”
Section: The Parameters By Which Molecular Mimicry Is Activated and Amentioning
confidence: 99%
See 1 more Smart Citation